Multi-Stakeholder Collaboration in Education Management to Achieve SDGs 2030 - M. Iqbal Abdurrahim (Pt. Anagata Sembagi Education, 2024)
This study aims to identify effective collaboration models in improving the quality of education, as well as assessing their impact on the achievement of SDG 4 (Quality Education) educational goals. This article aims to analyze the roles and challenges of collaboration between various stakeholders in effective education management efforts to support the achievement of the 2030 SDGs. In terms of research methods, the approach used is qualitative with case studies to explore in depth the roles and experiences of stakeholders in educational collaboration. Data collection was carried out through in-depth interviews with representatives from the government sector, the private sector, NGOs, and the community, as well as focus group discussions (FGD). The results of the study show that there are several effective collaboration models in improving education management, including cooperation between the government, the private sector, and the community. This collaboration has been proven to accelerate the achievement of SDG 4, by improving access and quality of education, as well as the relevance of curricula at various levels of education. However, the study also identified various factors that were inhibiting, such as a lack of coordination between stakeholders and differences in priorities between sectors